Timing and specificity of cotranslational nascent protein modification in bacteria - Yang, Chien-I (Proc Natl Acad Sci U S A, 2019)
The nascent polypeptide exit site of the ribosome is a crowded environment where multiple ribosome-associated protein biogenesis factors (RPBs) compete for the nascent polypeptide to influence their localization, folding, or quality control. Here we address how N-terminal methionine excision (NME), a ubiquitous process crucial for the maturation of over 50% of the bacterial proteome, occurs in a timely and selective manner in this crowded environment. In bacteria, NME is mediated by 2 essential enzymes, peptide deformylase (PDF) and methionine aminopeptidase (MAP). We show that the reaction of MAP on ribosome-bound nascent chains approaches diffusion-limited rates, allowing immediate methionine excision of optimal substrates after deformylation. Specificity is achieved by kinetic competition of NME with translation elongation and by regulation from other RPBs, which selectively narrow the processing time window for suboptimal substrates. A mathematical model derived from the data accurately predicts cotranslational NME efficiency in the cytosol. Our results demonstrate how a fundamental enzymatic activity is reshaped by its associated macromolecular environment to optimize both efficiency and selectivity, and provides a platform to study other cotranslational protein biogenesis pathways.